2010
DOI: 10.3892/ol.2010.197
|View full text |Cite
|
Sign up to set email alerts
|

Detection of fecal interferon-induced transmembrane protein messenger RNA for colorectal cancer screening

Abstract: Abstract. Interferon-induced transmembrane protein (IFITM) is reported to be frequently overexpressed in colorectal tumors. This study aimed to determine the usefulness of detecting fecal IFITM messenger RNA (mRNA) by real-time reverse-transcription polymerase chain reaction (RT-PCR) for colorectal cancer (CRC) screening. This pilot study included 21 patients with CRC and 23 healthy controls. Total RNA was isolated from the feces of the patients, and the expression levels of the mRNA of IFITM1, IFITM2 and IFIT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The corresponding mutations in CD225 structure have been found in our study. Tissues of colorectal cancer in humans were confirmed with over-expressed IFITM3, while IFITM3 knock-offs caused significant suppression of the proliferation, colony formation, and migration (37,38). Also, IFITM1 knock-offs significantly suppressed the invasiveness of head and neck tumor cells (31).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The corresponding mutations in CD225 structure have been found in our study. Tissues of colorectal cancer in humans were confirmed with over-expressed IFITM3, while IFITM3 knock-offs caused significant suppression of the proliferation, colony formation, and migration (37,38). Also, IFITM1 knock-offs significantly suppressed the invasiveness of head and neck tumor cells (31).…”
Section: Discussionmentioning
confidence: 91%
“…More and more studies have shown that IFITMs can be used as markers for tumor prognosis. IFITMs are reported to be frequently overexpressed in colorectal tumors (38), and the IFITMs family can be used as marker molecules for human colorectal cancer (39), and IFITM1 can be used as a rare type of squamous cell/ adenosquamous carcinoma (SC/ASC) and common adenocarcinoma (AC) marker molecule (40).…”
Section: Discussionmentioning
confidence: 99%
“…Early work suggested IFITM3 is a cancer biomarker, following observed overexpression in colonic cancers and gliomas (20,21). Subsequently, IFITM3 overexpression in cancer tissues as compared to healthy adjacent tissue was confirmed in other cancers, including colonic (22,23), gastric (24), breast (25), prostate (26), lung (27), and liver (28) (Figures 1B, C). IFITM3 expression is higher in metastatic lymph nodes and bone metastases when compared to primary tumors (23,26).…”
Section: Ifitm3 Expression In Cancer the Relationship Between Ifitm3 mentioning
confidence: 83%
“…Yang and co-workers found that IFITM2 has a high expression status in renal clear cell carcinoma tissues and cells, and can lead to tumor invasion and metastasis by promoting lymphangiogenesis (Yang et al, 2021). Some studies have reported that IFITM2 expression is remarkably elevated in patients with colorectal cancer, and it can be used as one of the molecular markers with high speci city and sensitivity for screening in patients (Chan et al, 2022;Miyamoto et al, 2011). Daniel and colleagues similarly found that IFITM2 is over-expressed in colon cancer, however, its mode of action is associated with tumor cell growth inhibition and apoptotic induction in a p53-independent manner(Daniel-Carmi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%